Role of metabolic dysfunction-associated fatty liver disease in atrial fibrillation and heart failure: molecular and clinical aspects - Cheung, Jamie; Cheung, Bernard Man-Yung; Yiu, Kai-Hang; Tse, Hung-Fat; Chan, Yap-Hang (Frontiers in Cardiovascular Medicine, 2025)
Metabolic dysfunction-associated fatty liver disease (MASLD) is a rising global health concern. In addition to direct hepatic complications, extra-hepatic complications, including cardiovascular diseases (CVD), type 2 diabetes (T2D), gastroesophageal reflux disease, chronic kidney disease and some malignancies, are increasingly recognized. CVD, including atrial fibrillation (AF) and heart failure (HF), is the leading cause of death in patients with MASLD. External factors, including excess energy intake, sedentary lifestyle and xenobiotic use, induce inflammation-related complications. MASLD, AF, and HF are associated with immune system activation, including the reprogramming of immune cells and the establishment of immune memory. Emerging evidence suggests that the heart and the liver cross-talk with each other through the diverse spectrum of autocrine, paracrine and endocrine mechanisms. Pro-inflammatory cytokines produced from the liver and the heart circulate systemically to orchestrate metabolic derangements that promote the systematic immune dysregulation in the heart-liver axis and the development of end-organ complications. Cardio-hepatic syndrome describes the clinical and biochemical evidence of hepatic dysfunction and cardiac pathology due to the interaction between the heart and the liver. Activation of inflammatory cascades, oxidative stress and immune system dysregulation underlie key mechanisms in bringing about such pathological changes. This review focuses on the current clinical and molecular evidence about the heart-liver cross-talk. It summarizes the epidemiological and pathophysiological associations of MASLD, AF and HF. In addition, we will discuss how repurposing currently available and emerging pharmacotherapies may help tackle the cardiovascular risks resulting from MASLD.